A high performance fastener and a heat treatment method for the fastener
By introducing ceramic doped intermediate alloy and surface B-C co-permeation treatment into the fasteners, the problem of insufficient performance of existing fasteners in harsh environments is solved, and fasteners with high hardness, high strength, excellent wear and heat resistance are achieved.
Patent Information
- Application Number
- CN202410214024.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-02-27
AI Technical Summary
In harsh environments or strict application scenarios, existing fasteners are difficult to meet the needs of high wear resistance, high temperature resistance, strength and corrosion resistance.
A ceramic doped intermediate alloy was used to prepare g-C3N4 by calcining urea to form a Ti(C,N)-(TiAl,Al)N@Fe metal cermet composite, and electroless plating and coating NiWCo alloy to prepare high-performance fasteners. At the same time, surface B-C co-permeation is performed to improve performance.
It significantly improves the hardness, strength, wear resistance, heat resistance and oxidation resistance of the fastener, and can meet the application needs of harsh environments and strict requirements.
Smart Images

Figure CN118064808B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fastener manufacturing, and in particular to a high-performance fastener and a heat treatment method for the fastener. Background Art
[0002] Fasteners are a widely used type of mechanical basic parts, including bolts, studs, screws, nuts, fastener washers, pins, rivets, etc. They are used in energy, electronics, electrical appliances, machinery, chemicals, metallurgy, molds, hydraulics, etc. Stainless steel fasteners have good overall performance and are one of the most widely used fastener materials. However, in some special scenarios with harsh application environments or strict requirements, such as aviation equipment, flight equipment, engines, and navigation equipment, there are higher requirements for the wear resistance, high temperature resistance, strength, and corrosion resistance of fasteners, and conventional stainless steel fasteners are often difficult to meet the requirements.
[0003] Patent CN116200668B discloses a heat-resistant high-strength fastener material and a preparation method thereof. The fastener material is obtained by making certain adjustments based on the existing 304 stainless steel composition. The fastener material prepared by the adjustment is not only more corrosion-resistant and can cope with the high-chlorine environment at the seaside, but its strength and hardness still need to be improved.
[0004] Patent CN102260830B discloses a processing method and heat treatment process for high-strength fasteners, which can improve the strength and toughness of steel-based fasteners by adjusting material matching and preparation process, but it does not reliably improve wear resistance and high temperature resistance.
[0005] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a high-performance fastener and a heat treatment method for the fastener in view of the deficiencies in the above-mentioned prior art.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a high-performance fastener, the raw materials for its preparation include, by weight percentage:
[0008] C: 0.12-0.33%, Si: 0.23-0.48%, Mn: 0.62-0.77%, Cr: 2.32-4.14%, Ni: 4.11-6.32%, Re: 0.005-0.022%, ceramic-doped master alloy: 4.2-13.5%, the balance is Fe and unavoidable impurity elements;
[0009] The ceramic-doped master alloy is prepared by the following method:
[0010] 1) Preparation of g-C3N4 by calcining urea;
[0011] 2) Preparation of g-C3N4-AlFeO composite precursor using g-C3N4;
[0012] 3) Prepare Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite by thermal reduction method using g-C3N4-AlFeO composite precursor;
[0013] 4) The metal-ceramic composite is coated with NiWCo alloy by chemical plating to prepare the ceramic-doped master alloy.
[0014] Preferably, the ceramic-doped master alloy is prepared by the following method:
[0015] 1) Preparation of g-C3N4 by calcining urea:
[0016] Place urea in a muffle furnace, heat to 550-650°C at 5-10°C / min, and calcine for 3-5h to obtain g-C3N4;
[0017] 2) Preparation of g-C3N4-TiAlFeO composite precursor using g-C3N4:
[0018] 0.42-3.15 g g-C3N4, 0.0073-0.0294 mol butyl titanate, 0.03-0.2 mol ferric acetate, and 0.0025-0.01 mol aluminum acetate are mixed and ground for 45-90 min, the resulting mixture is calcined at 600-700 ° C for 1-4 h, cooled to room temperature, and the product is ground to obtain a g-C3N4-TiAlFeO composite precursor;
[0019] 3) Preparation of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite by thermal reduction method using g-C3N4-TiAlFeO composite precursor:
[0020] The g-C3N4-TiAlFeO composite precursor is added into a tubular vacuum furnace, reacted at 950-1150°C for 1-4 hours in a hydrogen atmosphere, cooled to room temperature, and ground to obtain a Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite;
[0021] 4) Electrolessly coating the metal-ceramic composite with NiWCo alloy to prepare the ceramic-doped master alloy:
[0022] 4-1) washing the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite prepared in step 3) with a hydrochloric acid solution, then washing with deionized water until neutral, then washing with ethanol, and drying;
[0023] 4-2) adding the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite pretreated in step 4-1) to a 5-20 g / L SnCl2 solution for 5-25 min, taking it out, washing it with deionized water, adding it to the plating solution, stirring it for 2-10 min, heating it to 70-80°C, controlling the pH value of the plating solution to 10-11, plating it for 40-90 min, letting it stand for 5-20 min after completion, filtering it, washing the solid product with deionized water, and drying it to obtain a ceramic doped intermediate alloy.
[0024] Preferably, in step 4-2), the loading amount of the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite in the plating solution is 5-25 g / L of plating solution.
[0025] Preferably, the components of the plating solution include: 20-38 g / L nickel sulfate, 5-15 g / L sodium tungstate, 6-18 g / L cobalt sulfate, 30-45 g / L sodium hypophosphite, 10-30 g / L sodium citrate, 6-15 g / L ammonium chloride, and 13-34 g / L EDTA.
[0026] Preferably, the ceramic-doped master alloy comprises the following components by weight percentage:
[0027] Ti: 7.05-19.24%, Al: 1.91-4.40%, Ni: 12.06-24.25%, W: 7.18-12.45%, Co: 5.43-8.62%, C: 3.16-6.04%, N: 4.95-8.97%, and the balance is Fe and inevitable impurity elements.
[0028] Preferably, the ceramic-doped master alloy is prepared by the following method:
[0029] 1) Preparation of g-C3N4 by calcining urea:
[0030] Place urea in a muffle furnace, heat to 580 °C at 10 °C / min, and calcine for 3.5 h to obtain g-C3N4;
[0031] 2) Preparation of g-C3N4-TiAlFeO composite precursor using g-C3N4:
[0032] 0.85 g g-C3N4, 0.0147 mol butyl titanate, 0.065 mol ferric acetate, and 0.005 mol aluminum acetate were mixed and ground for 60 min, and the resulting mixture was calcined at 650 ° C for 2 h, cooled to room temperature, and the product was ground to obtain a g-C3N4-TiAlFeO composite precursor;
[0033] 3) Preparation of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite by thermal reduction method using g-C3N4-TiAlFeO composite precursor:
[0034] The g-C3N4-TiAlFeO composite precursor was added into a tubular vacuum furnace, reacted at 1050°C for 2 h in a hydrogen atmosphere, cooled to room temperature, and ground to obtain a Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite.
[0035] 4) Electrolessly coating the metal-ceramic composite with NiWCo alloy to prepare the ceramic-doped master alloy:
[0036] 4-1) washing the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite prepared in step 3) with a 5% by mass hydrochloric acid solution, then washing with deionized water until neutral, then washing with ethanol, and drying at 90° C.;
[0037] 4-2) The Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite pretreated in step 4-1) was added to a 12 g / L SnCl2 solution for 10 min, taken out, washed with deionized water, dried, added to the plating solution, stirred for 5 min, heated to 75°C, the pH value of the plating solution was controlled to 10, and the plating was performed for 60 min. After the completion, it was allowed to stand for 10 min, filtered, and the solid product was washed with deionized water and dried at 60°C for 5 h to obtain a ceramic doped intermediate alloy.
[0038] Preferably, in step 4-2), the loading amount of the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite in the plating solution is 10 g / L plating solution;
[0039] The components of the plating solution include: 30g / L nickel sulfate, 10g / L sodium tungstate, 12g / L cobalt sulfate, 40g / L sodium hypophosphite, 20g / L sodium citrate, 10g / L ammonium chloride, and 25g / L EDTA.
[0040] Preferably, the ceramic-doped master alloy comprises the following components by weight percentage:
[0041] Ti: 14.11%, Al: 2.70%, Ni: 17.12%, W: 9.39%, Co: 6.86%, C: 4.52%, N: 7.26%, and the remainder is Fe and inevitable impurity elements.
[0042] Preferably, the method for preparing the high-performance fastener comprises the following steps:
[0043] Step 1: weigh the raw materials according to weight ratio: carbon, silicon, manganese, chromium, nickel, rhenium and ceramic-doped master alloy;
[0044] Step 2, smelting: add all raw materials into a vacuum induction furnace, smelt at 1300-1550°C for 20-45min, and then perform LF refining and degassing to obtain molten steel;
[0045] Step 3: Casting: Cast the molten steel into shape and machine it to obtain high-performance fasteners.
[0046] The present invention also provides a heat treatment method for the high-performance fastener as described above, comprising the following steps:
[0047] S1. Keep the high-performance fasteners at 800-900℃ for 2-6h, then oil cool to 120-180℃ and keep for 1-3h;
[0048] S2. Surface chemical heat treatment:
[0049] After grinding, cleaning and drying, high-performance fasteners are placed in a container, embedded with co-penetration powder, sealed, and heated at 850-1000℃ for 8-12h for BC co-penetration;
[0050] The co-penetration powder is prepared by the following method: according to mass percentage, 20-28% of borax, 10-15% of boron carbide, 3-8% of ammonium chloride, 1.5-5% of potassium fluoroborate, 0.5-2% of yttrium oxide, 0.5-1.5% of lanthanum oxide and the balance of charcoal are mixed, and ball milled for 1-4 hours to obtain the co-penetration powder;
[0051] S3, cool down to 700-800℃, keep warm for 0.5-3h, oil cool to 70-90℃;
[0052] S4. Heat to 180-270℃ for tempering, keep warm for 1-5h, and then air cool to room temperature.
[0053] The beneficial effects of the present invention are:
[0054] The present invention provides a high-performance fastener and a heat treatment method thereof. By adjusting the chemical composition and improving the process, a fastener with high strength, high wear resistance, excellent high temperature resistance and corrosion resistance can be obtained, thereby meeting the use requirements in some special scenarios with relatively harsh application environments or relatively strict requirements.
[0055] The present invention introduces a large amount of ceramic alloy phases, such as Ti(C, N), TiAlN, and AlN, which can be evenly dispersed in the matrix, into the steel matrix material of the high-performance fastener by using ceramic-doped master alloys, thereby overcoming the traditional application difficulties of ceramic particles and significantly improving the hardness, strength, friction resistance, heat resistance, and oxidation resistance of the high-performance fastener.
[0056] In the present invention, by performing BC co-penetration treatment on the surface of the high-performance fastener, its hardness, friction resistance, oxidation resistance and corrosion resistance can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 is the XRD spectrum of the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite prepared in Example 1 of the present invention;
[0058] Figure 2 The high temperature strength test results of the present invention are as follows;
[0059] Figure 3 1 is the high temperature wear test result of the present invention. DETAILED DESCRIPTION
[0060] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0061] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0062] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0063] The present invention provides a high-performance fastener, the raw materials for its preparation include, by weight percentage:
[0064] C: 0.12-0.33%, Si: 0.23-0.48%, Mn: 0.62-0.77%, Cr: 2.32-4.14%, Ni: 4.11-6.32%, Re: 0.005-0.022%, ceramic-doped master alloy: 4.2-13.5%, the balance is Fe and unavoidable impurity elements.
[0065] The preparation method comprises the following steps:
[0066] Step 1: Weigh powder raw materials according to weight ratio: carbon, silicon, manganese, chromium, nickel, rhenium and ceramic-doped master alloy;
[0067] Step 2, smelting: add all raw materials into a vacuum induction furnace, smelt at 1300-1550°C for 20-45min, and then perform LF refining and degassing to obtain molten steel;
[0068] Step 3: Casting: Cast the molten steel into shape and machine it to obtain high-performance fasteners.
[0069] The present invention also heat treats the prepared high-performance fastener according to the following method to further improve its comprehensive performance. The specific steps include:
[0070] S1. Keep the high-performance fasteners at 800-900℃ for 2-6h, then oil cool to 120-180℃ and keep for 1-3h;
[0071] S2. Surface chemical heat treatment:
[0072] After grinding, cleaning and drying, high-performance fasteners are placed in a container, embedded with co-penetration powder, sealed, and heated at 850-1000℃ for 8-12h for BC co-penetration;
[0073] The co-penetration powder is prepared by the following method: according to mass percentage, 20-28% of borax, 10-15% of boron carbide, 3-8% of ammonium chloride, 1.5-5% of potassium fluoroborate, 0.5-2% of yttrium oxide, 0.5-1.5% of lanthanum oxide and the balance of charcoal are mixed, and ball milled for 1-4 hours to obtain the co-penetration powder;
[0074] S3, cool down to 700-800℃, keep warm for 0.5-3h, oil cool to 70-90℃;
[0075] S4. Heat to 180-270℃ for tempering, keep warm for 1-5h, and then air cool to room temperature.
[0076] The fasteners in the present invention can be various conventional products that play a role in fastening and connecting, such as bolts, studs, screws, screws, nuts, fastening washers, pins, rivets, etc.
[0077] In the present invention, the ceramic-doped master alloy is prepared by the following method:
[0078] 1) Preparation of g-C3N4 by calcining urea:
[0079] Place urea in a muffle furnace, heat to 550-650°C at 5-10°C / min, and calcine for 3-5h to obtain g-C3N4;
[0080] 2) Preparation of g-C3N4-TiAlFeO composite precursor using g-C3N4:
[0081] 0.42-3.15 g g-C3N4, 0.0073-0.0294 mol butyl titanate, 0.03-0.2 mol ferric acetate, and 0.0025-0.01 mol aluminum acetate are mixed and ground for 45-90 min, the resulting mixture is calcined at 600-700 ° C for 1-4 h, cooled to room temperature, and the product is ground to obtain a g-C3N4-TiAlFeO composite precursor;
[0082] 3) Preparation of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite by thermal reduction method using g-C3N4-TiAlFeO composite precursor:
[0083] The g-C3N4-TiAlFeO composite precursor is added into a tubular vacuum furnace, reacted at 950-1150°C for 1-4 hours in a hydrogen atmosphere, cooled to room temperature, and ground to obtain a Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite;
[0084] 4) Electrolessly coating the metal-ceramic composite with NiWCo alloy to prepare a ceramic-doped master alloy:
[0085] 4-1) washing the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite prepared in step 3) with a hydrochloric acid solution, then washing with deionized water until neutral, then washing with ethanol, and drying;
[0086] 4-2) adding the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite pretreated in step 4-1) to a 5-20 g / L SnCl2 solution for 5-25 min, taking it out, washing it with deionized water, adding it to the plating solution, stirring it for 2-10 min, heating it to 70-80°C, controlling the pH value of the plating solution to 10-11, plating it for 40-90 min, letting it stand for 5-20 min after completion, filtering it, washing the solid product with deionized water, and drying it to obtain a ceramic doped intermediate alloy.
[0087] In a preferred embodiment, in step 4-2), the loading amount of the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite in the plating solution is 5-25 g / L of plating solution.
[0088] In a preferred embodiment, the components of the plating solution include: 20-38 g / L nickel sulfate, 5-15 g / L sodium tungstate, 6-18 g / L cobalt sulfate, 30-45 g / L sodium hypophosphite, 10-30 g / L sodium citrate, 6-15 g / L ammonium chloride, and 13-34 g / L EDTA.
[0089] In a preferred embodiment, the ceramic-doped master alloy comprises the following components by weight percentage:
[0090] Ti: 7.05-19.24%, Al: 1.91-4.40%, Ni: 12.06-24.25%, W: 7.18-12.45%, Co: 5.43-8.62%, C: 3.16-6.04%, N: 4.95-8.97%, the remainder is Fe and inevitable impurity elements, and the sum of the contents of each component in the ceramic-doped master alloy is 100%.
[0091] Among the components of the present invention, manganese can improve the high-temperature strength of steel; chromium can improve the strength and hardness of steel, and can improve high-temperature mechanical properties, corrosion resistance and oxidation resistance; nickel can improve the strength of steel without significantly reducing its toughness, and nickel can also improve the corrosion resistance of steel, not only being acid-resistant, but also being resistant to alkali and atmospheric corrosion; rhenium can improve the oxidation resistance, high-temperature strength and corrosion resistance of the base material; in addition, it can have a certain reinforcing effect on W and improve plasticity.
[0092] In the composition of the present invention, a large amount of ceramic alloy phases that can be evenly dispersed in the matrix are introduced into the steel matrix material of the high-performance fasteners by ceramic-doped master alloys: Ti(C, N), TiAlN, AlN, etc., which can overcome the traditional application difficulties of ceramic particles and can greatly improve the hardness, strength, friction resistance, heat resistance and oxidation resistance of high-performance fasteners. The main mechanism is explained below in combination with the preparation method of the ceramic-doped master alloy.
[0093] 1. The present invention firstly prepares yellow blocky g-C3N4 by the traditional method of calcining urea (Ma Yujie, Cui Lifeng. Preparation and adsorption properties of TiN-TiC composite materials [J]. Nonferrous Metal Materials and Engineering, 2019, 40(4):5. DOI:CNKI:SUN:SHHA.0.2019-04-001.);
[0094] 2. Then, g-C3N4 is reacted with butyl titanate, ferrous acetate and aluminum acetate at high temperature to form a composite precursor g-C3N4-AlFeO doped with titanium, iron and aluminum oxides and g-C3N4;
[0095] 3. Then, the oxides of titanium, iron and aluminum in the composite precursor gg-C3N4-AlFeO are reduced under the action of high temperature and reducing gas to form titanium-doped iron-aluminum composite core particles. C and N decomposed by g-C3N4 at high temperature form TiC, TiN and their composite particles with titanium, which are evenly coated on the surface of the iron-aluminum composite core particles, and finally form a metal ceramic composite with a core carrier with iron-aluminum alloy as the main component and Ti(C,N) and (TiAl,Al)N (i.e., TiAlN and AlN) ceramic alloy particles as the outer layer load coated with a core-shell structure: Ti(C,N)-TiAlN@Fe.
[0096] In this process, C and Ti generate TiC phase, N and Ti generate TiN phase, and N and Al generate AlN; TiC phase and TiN phase belong to isomorphic structures, and C atoms in the TiC lattice can be replaced by N atoms in any proportion to form a continuous solid solution phase Ti(C,N), so the system of the present invention contains TiC, TiN, and Ti(C,N) mixed ceramic phases. Ti(C,N) has the advantages of both TiC and TiN, and also has higher oxidation resistance, hardness, wear resistance and heat resistance than them.
[0097] The formation of AlN phase has a strengthening effect on promoting grain refinement, which can improve hardness and strength and enhance friction resistance. Al can replace some Ti atoms located at the face center of TiN face-centered cubic structure to form TiAlN phase, which distorts the lattice and increases the number of grain boundaries. At the same time, the number of dislocations increases and is not easy to slip, so that the hardness and strength are improved. In addition, part of Al can efficiently form Ni3Al, Ni3 (AlTi) and other dispersion strengthening phases with Ni in the subsequent NiWCo alloy coating during the subsequent smelting process. Ni, as a bonding phase, promotes the compatibility of ceramic particles and the matrix, and Al dissolved in the bonding phase has a strengthening effect on the bonding phase, making it difficult for the hard ceramic phase particles to "plow" relative to the matrix during the friction process, reducing the amount of friction and wear, thereby improving the friction resistance.
[0098] As the main component of the core, Fe can play the following two roles:
[0099] First aspect:
[0100] The ceramic alloy particles Ti(C,N), TiAlN and AlN are loaded by core microspheres with Fe as the main component, which can reduce the agglomeration of the metal-ceramic composite during the chemical plating process, and are conducive to fully coating the NiWCo alloy coating on the surface of the ceramic alloy particles;
[0101] Second aspect:
[0102] Ceramic particles, such as TiC, TiN and the above-mentioned Ti(C,N), TiAlN, etc., have poor wettability with the iron matrix. For example, the wetting angle of TiC to liquid Fe is 41° in a vacuum atmosphere at 1550°C (Huang Boyun. Principles of Powder Metallurgy [M], Beijing: Metallurgical Industry Press, 2002.). This natural defect will lead to the situation that it is difficult to disperse it evenly in the metal matrix, the particle size is coarse, and the interface bonding strength with the matrix is not high, making it difficult for the ceramic particles to fully exert their reinforcing effect on the matrix; in addition, the density difference between ceramic particles and the iron matrix is large and they are easy to float in the molten steel, resulting in macroscopic segregation in their distribution.
[0103] The present invention can overcome the above problems by forming a structure in which a core loaded with ceramic alloy particles with Fe as the main component and a NiWCo alloy coating is coated on the surface of the ceramic alloy particles: NiWCo@Ti(C,N)-TiAlN@Fe. Firstly, in this structural system, the introduction of Fe and NiWCo alloy coating can improve the overall density, reduce the density difference between the ceramic-doped intermediate alloy and the molten steel, and reduce the macro-segregation of the ceramic alloy particles; secondly, when the ceramic-doped intermediate alloy contacts the molten steel, Fe melts into the molten steel as a binder, and the ceramic-doped intermediate alloy particles are separated from the binder Fe, wetted by the molten steel and retained in the molten steel, thereby helping to make the ceramic alloy particles more evenly dispersed in the molten steel.
[0104] 4. Finally, the present invention coats a NiWCo alloy coating on a metal ceramic composite: Ti(C, N)-TiAlN@Fe by a chemical plating method to obtain a ceramic doped intermediate alloy of a core-shell structure system in which a core-loaded ceramic alloy particle and a surface of an outer shell ceramic alloy particle are further coated with a NiWCo alloy coating: NiWCo@Ti(C, N)-TiAlN@Fe;
[0105] W, Ni and Co together form an alloy coating layer NiWCo, which can further improve the wettability of the ceramic alloy particles and the matrix, reduce the agglomeration of the ceramic alloy particles, and reduce the agglomeration growth during high temperature.
[0106] Among them, W has good compatibility with ceramic alloy particles. W is coated on the ceramic alloy particles in the form of a coating component, which can promote W and ceramic alloy particles to exist in the matrix system in a fully and uniformly mixed state, so that the following benefits can be obtained: Ti (C, N) phase is dispersed on the W grain boundary, which plays a role in pinning the grain boundary and increasing the resistance to grain boundary migration, thereby hindering the aggregation and growth of W particles during high temperature, playing a role in refining W grains, and is more conducive to the reinforcement of W on the matrix; on the other hand, since W can exist in a uniformly mixed state with ceramic alloy particles, it is more conducive to the formation of WC phase between W and the free state C in the ceramic alloy particles during high temperature, and the WC phase can further improve the wear resistance, hardness and thermal strength of the material.
[0107] Among them, Ni, as the main alloy coating component, has good compatibility with iron and can be completely dissolved in any proportion at high temperature. The coating of Ni on ceramic alloy particles can improve the wettability between them and molten steel, so that they can be evenly dispersed in the matrix, and can improve the bonding strength between the ceramic alloy and the matrix interface; Ni can exist in the matrix system in a uniformly mixed state with the ceramic alloy. In the matrix system, Ni can not only improve the heat resistance, corrosion resistance and strength, but also improve the toughness of the matrix, thereby compensating for the increase in brittleness caused by the ceramic alloy particles and the reinforcing phases such as the WC phase;
[0108] Among them, Co in the coating composition can provide good anti-oxidation performance and prevent the ceramic-doped intermediate alloy from oxidizing; after entering the matrix, Co can improve the thermal strength and high-temperature hardness.
[0109] In the present invention, by performing BC co-penetration treatment on the surface of the high-performance fastener, its hardness, friction resistance, oxidation resistance and corrosion resistance can be further improved.
[0110] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0111] Example 1
[0112] A high-performance fastener, the raw materials for its preparation include, by weight percentage:
[0113] C: 0.17%, Si: 0.35%, Mn: 0.64%, Cr: 3.27%, Ni: 5.38%, Re: 0.0075%, ceramic-doped master alloy: 8.5%, the balance is Fe and unavoidable impurity elements;
[0114] The preparation method comprises the following steps:
[0115] Step 1: weigh the raw materials according to weight ratio: carbon, silicon, manganese, chromium, nickel, rhenium and ceramic-doped master alloy;
[0116] Step 2, smelting: add all raw materials into a vacuum induction furnace, smelt at 1520°C for 30 minutes, and then perform LF refining and degassing to obtain molten steel;
[0117] Step 3: Casting: Pour the molten steel into a mold, cool it to room temperature at a rate of 15°C / min under an argon atmosphere, demold it to obtain an ingot, and then machine it to obtain a high-performance fastener.
[0118] Furthermore, in this embodiment, the prepared high-performance fastener is heat treated according to the following method to further improve its comprehensive performance. The specific steps include:
[0119] S1. Keep the high-performance fastener at 850℃ for 4 hours, then oil cool to 155℃ and keep it for 2 hours;
[0120] S2. Chemical heat treatment:
[0121] After grinding, cleaning and drying, high-performance fasteners are placed in a container, embedded with co-penetration powder, sealed, and heated at 900°C for 10 hours for BC co-penetration treatment;
[0122] The co-penetration powder is prepared by the following method: according to mass percentage, 25% of borax, 12% of boron carbide, 5% of ammonium chloride, 3.5% of potassium fluoroborate, 1.5% of yttrium oxide, 1% of lanthanum oxide and the remainder of charcoal are mixed, and ball milled for 2 hours to obtain the co-penetration powder;
[0123] S3, cool down to 750℃, keep warm for 1h, and oil cool to 80℃;
[0124] S4. Heat to 200°C for tempering treatment, keep warm for 3 hours, and then air cool to room temperature to obtain a high-performance fastener product after heat treatment.
[0125] In this embodiment, the ceramic-doped master alloy is prepared by the following method:
[0126] 1) Preparation of g-C3N4 by calcining urea:
[0127] Place urea in a muffle furnace, heat to 580 °C at 10 °C / min, and calcine for 3.5 h to obtain g-C3N4;
[0128] 2) Preparation of g-C3N4-TiAlFeO composite precursor using g-C3N4:
[0129] 0.85 g g-C3N4, 0.0147 mol butyl titanate, 0.065 mol ferric acetate, and 0.005 mol aluminum acetate were mixed and ground for 60 min, and the resulting mixture was calcined at 650 ° C for 2 h, cooled to room temperature, and the product was ground to obtain a g-C3N4-TiAlFeO composite precursor;
[0130] 3) Preparation of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite by thermal reduction method using g-C3N4-TiAlFeO composite precursor:
[0131] The g-C3N4-TiAlFeO composite precursor was added into a tubular vacuum furnace, reacted at 1050°C for 2 h in a hydrogen atmosphere, cooled to room temperature, and ground to obtain a Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite.
[0132] 4) Electrolessly coating the metal-ceramic composite with NiWCo alloy to prepare a ceramic-doped master alloy:
[0133] 4-1) washing the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite prepared in step 3) with a 5% by mass hydrochloric acid solution, then washing with deionized water until neutral, then washing with ethanol, and drying at 90° C.;
[0134] 4-2) The Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite pretreated in step 4-1) was added to a 12 g / L SnCl2 solution for 10 min, taken out, washed with deionized water, dried, added to the plating solution, stirred for 5 min, heated to 75°C, the pH value of the plating solution was controlled to 10, and the plating was performed for 60 min. After the completion, it was allowed to stand for 10 min, filtered, and the solid product was washed with deionized water and dried at 60°C for 5 h to obtain a ceramic doped intermediate alloy.
[0135] In step 4-2), the loading amount of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite in the plating solution is 10 g / L plating solution; the components of the plating solution include: 30 g / L nickel sulfate, 10 g / L sodium tungstate, 12 g / L cobalt sulfate, 40 g / L sodium hypophosphite, 20 g / L sodium citrate, 10 g / L ammonium chloride, and 25 g / L EDTA.
[0136] The ceramic-doped master alloy includes the following components by weight percentage:
[0137] Ti: 14.11%, Al: 2.70%, Ni: 17.12%, W: 9.39%, Co: 6.86%, C: 4.52%, N: 7.26%, and the remainder is Fe and inevitable impurity elements.
[0138] Example 2
[0139] A high-performance fastener, the raw materials for its preparation include, by weight percentage:
[0140] C: 0.21%, Si: 0.35%, Mn: 0.64%, Cr: 3.27%, Ni: 6.05%, Re: 0.0075%, ceramic-doped master alloy: 7%, the balance is Fe and unavoidable impurity elements;
[0141] The preparation method comprises the following steps:
[0142] Step 1: weigh the raw materials according to weight ratio: carbon, silicon, manganese, chromium, nickel, rhenium and ceramic-doped master alloy;
[0143] Step 2, smelting: add all raw materials into a vacuum induction furnace, smelt at 1520°C for 30 minutes, and then perform LF refining and degassing to obtain molten steel;
[0144] Step 3: Casting: Pour the molten steel into a mold, cool it to room temperature at a rate of 15°C / min under an argon atmosphere, demold it to obtain an ingot, and then machine it to obtain a high-performance fastener.
[0145] Furthermore, in this embodiment, the prepared high-performance fastener is heat treated according to the following method to further improve its comprehensive performance. The specific steps include:
[0146] S1. Keep the high-performance fastener at 850℃ for 4 hours, then oil cool to 155℃ and keep it for 2 hours;
[0147] S2. Chemical heat treatment:
[0148] After grinding, cleaning and drying, high-performance fasteners are placed in a container, embedded with co-penetration powder, sealed, and heated at 900°C for 10 hours for BC co-penetration treatment;
[0149] The co-penetration powder is prepared by the following method: according to mass percentage, 25% of borax, 12% of boron carbide, 5% of ammonium chloride, 3.5% of potassium fluoroborate, 1.5% of yttrium oxide, 1% of lanthanum oxide and the remainder of charcoal are mixed, and ball milled for 2 hours to obtain the co-penetration powder;
[0150] S3, cool down to 750℃, keep warm for 1h, and oil cool to 80℃;
[0151] S4. Heat to 200°C for tempering treatment, keep warm for 3 hours, and then air cool to room temperature to obtain a high-performance fastener product after heat treatment.
[0152] In this embodiment, the ceramic-doped master alloy is prepared by the following method:
[0153] 1) Preparation of g-C3N4 by calcining urea:
[0154] Place urea in a muffle furnace, heat to 580 °C at 10 °C / min, and calcine for 3.5 h to obtain g-C3N4;
[0155] 2) Preparation of g-C3N4-TiAlFeO composite precursor using g-C3N4:
[0156] 0.85 g g-C3N4, 0.0147 mol butyl titanate, 0.065 mol ferric acetate, and 0.005 mol aluminum acetate were mixed and ground for 60 min, and the resulting mixture was calcined at 650 ° C for 2 h, cooled to room temperature, and the product was ground to obtain a g-C3N4-TiAlFeO composite precursor;
[0157] 3) Preparation of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite by thermal reduction method using g-C3N4-TiAlFeO composite precursor:
[0158] The g-C3N4-TiAlFeO composite precursor was added into a tubular vacuum furnace, reacted at 1050°C for 2 h in a hydrogen atmosphere, cooled to room temperature, and ground to obtain a Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite.
[0159] 4) Electrolessly coating the metal-ceramic composite with NiWCo alloy to prepare a ceramic-doped master alloy:
[0160] 4-1) washing the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite prepared in step 3) with a 5% by mass hydrochloric acid solution, then washing with deionized water until neutral, then washing with ethanol, and drying at 90° C.;
[0161] 4-2) The Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite pretreated in step 4-1) was added to a 12 g / L SnCl2 solution for 10 min, taken out, washed with deionized water, dried, added to the plating solution, stirred for 5 min, heated to 75°C, the pH value of the plating solution was controlled to 10, and the plating was performed for 60 min. After the completion, it was allowed to stand for 10 min, filtered, and the solid product was washed with deionized water and dried at 60°C for 5 h to obtain a ceramic doped intermediate alloy.
[0162] In step 4-2), the loading amount of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite in the plating solution is 10 g / L plating solution; the components of the plating solution include: 30 g / L nickel sulfate, 10 g / L sodium tungstate, 12 g / L cobalt sulfate, 40 g / L sodium hypophosphite, 20 g / L sodium citrate, 10 g / L ammonium chloride, and 25 g / L EDTA.
[0163] The ceramic-doped master alloy includes the following components by weight percentage:
[0164] Ti: 14.11%, Al: 2.70%, Ni: 17.12%, W: 9.39%, Co: 6.86%, C: 4.52%, N: 7.26%, and the remainder is Fe and inevitable impurity elements.
[0165] Example 3
[0166] A high-performance fastener, the raw materials for its preparation include, by weight percentage:
[0167] C: 0.15%, Si: 0.33%, Mn: 0.68%, Cr: 3.14%, Ni: 5.22%, Re: 0.0075%, ceramic-doped master alloy: 9.0%, the balance is Fe and unavoidable impurity elements;
[0168] The preparation method comprises the following steps:
[0169] Step 1: weigh the raw materials according to weight ratio: carbon, silicon, manganese, chromium, nickel, rhenium and ceramic-doped master alloy;
[0170] Step 2, smelting: add all raw materials into a vacuum induction furnace, smelt at 1520°C for 30 minutes, and then perform LF refining and degassing to obtain molten steel;
[0171] Step 3: Casting: Pour the molten steel into a mold, cool it to room temperature at a rate of 15°C / min under an argon atmosphere, demold it to obtain an ingot, and then machine it to obtain a high-performance fastener.
[0172] Furthermore, in this embodiment, the prepared high-performance fastener is heat treated according to the following method to further improve its comprehensive performance. The specific steps include:
[0173] S1. Keep the high-performance fastener at 850℃ for 4 hours, then oil cool to 155℃ and keep it for 2 hours;
[0174] S2. Chemical heat treatment:
[0175] After grinding, cleaning and drying, high-performance fasteners are placed in a container, embedded with co-penetration powder, sealed, and heated at 900°C for 10 hours for BC co-penetration treatment;
[0176] The co-penetration powder is prepared by the following method: according to mass percentage, 25% of borax, 12% of boron carbide, 5% of ammonium chloride, 3.5% of potassium fluoroborate, 1.5% of yttrium oxide, 1% of lanthanum oxide and the remainder of charcoal are mixed, and ball milled for 2 hours to obtain the co-penetration powder;
[0177] S3, cool down to 750℃, keep warm for 1h, and oil cool to 80℃;
[0178] S4. Heat to 200°C for tempering treatment, keep warm for 3 hours, and then air cool to room temperature to obtain a high-performance fastener product after heat treatment.
[0179] In this embodiment, the ceramic-doped master alloy is prepared by the following method:
[0180] 1) Preparation of g-C3N4 by calcining urea:
[0181] Place urea in a muffle furnace, heat to 580 °C at 10 °C / min, and calcine for 3.5 h to obtain g-C3N4;
[0182] 2) Preparation of g-C3N4-TiAlFeO composite precursor using g-C3N4:
[0183] 0.85 g g-C3N4, 0.0147 mol butyl titanate, 0.065 mol ferric acetate, and 0.005 mol aluminum acetate were mixed and ground for 60 min, and the resulting mixture was calcined at 650 ° C for 2 h, cooled to room temperature, and the product was ground to obtain a g-C3N4-TiAlFeO composite precursor;
[0184] 3) Preparation of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite by thermal reduction method using g-C3N4-TiAlFeO composite precursor:
[0185] The g-C3N4-TiAlFeO composite precursor was added into a tubular vacuum furnace, reacted at 1050°C for 2 h in a hydrogen atmosphere, cooled to room temperature, and ground to obtain a Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite.
[0186] 4) Electrolessly coating the metal-ceramic composite with NiWCo alloy to prepare a ceramic-doped master alloy:
[0187] 4-1) washing the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite prepared in step 3) with a 5% by mass hydrochloric acid solution, then washing with deionized water until neutral, then washing with ethanol, and drying at 90° C.;
[0188] 4-2) The Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite pretreated in step 4-1) was added to a 12 g / L SnCl2 solution for 10 min, taken out, washed with deionized water, dried, added to the plating solution, stirred for 5 min, heated to 75°C, the pH value of the plating solution was controlled to 10, and the plating was performed for 60 min. After the completion, it was allowed to stand for 10 min, filtered, and the solid product was washed with deionized water and dried at 60°C for 5 h to obtain a ceramic doped intermediate alloy.
[0189] In step 4-2), the loading amount of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite in the plating solution is 10 g / L plating solution; the components of the plating solution include: 30 g / L nickel sulfate, 10 g / L sodium tungstate, 12 g / L cobalt sulfate, 40 g / L sodium hypophosphite, 20 g / L sodium citrate, 10 g / L ammonium chloride, and 25 g / L EDTA.
[0190] The ceramic-doped master alloy includes the following components by weight percentage:
[0191] Ti: 14.11%, Al: 2.70%, Ni: 17.12%, W: 9.39%, Co: 6.86%, C: 4.52%, N: 7.26%, and the remainder is Fe and inevitable impurity elements.
[0192] Comparative Example 1
[0193] A high-performance fastener, the raw materials for its preparation include, by weight percentage:
[0194] C: 0.17%, Si: 0.35%, Mn: 0.64%, Cr: 3.27%, Ni: 6.83%, W: 0.79%, Co: 0.58%, Re: 0.0075%, the balance is Fe and unavoidable impurity elements;
[0195] The preparation method comprises the following steps:
[0196] Step 1: weigh the raw materials according to weight ratio: carbon, silicon, manganese, chromium, nickel, rhenium and TiC;
[0197] Step 2, smelting: add all raw materials into a vacuum induction furnace, smelt at 1520°C for 30 minutes, and then perform LF refining and degassing to obtain molten steel;
[0198] Step 3: Casting: Pour the molten steel into a mold, cool it to room temperature at a rate of 15°C / min under an argon atmosphere, demold it to obtain an ingot, and then machine it to obtain a high-performance fastener.
[0199] Furthermore, in this example, the prepared high-performance fasteners are heat treated according to the following method to further improve their comprehensive performance. The specific method is the same as that in Example 1.
[0200] Comparative Example 2
[0201] A high-performance fastener, the raw materials for its preparation include, by weight percentage:
[0202] C: 0.17%, Si: 0.35%, Mn: 0.64%, Cr: 3.27%, Ni: 6.83%, W: 0.79%, Co: 0.58%, Re: 0.0075%, TiC: 1.27%, the balance is Fe and unavoidable impurity elements;
[0203] The preparation method comprises the following steps:
[0204] Step 1: weigh the raw materials according to weight ratio: carbon, silicon, manganese, chromium, nickel, rhenium and TiC;
[0205] Step 2, smelting: add all raw materials into a vacuum induction furnace, smelt at 1520°C for 30 minutes, and then perform LF refining and degassing to obtain molten steel;
[0206] Step 3: Casting: Pour the molten steel into a mold, cool it to room temperature at a rate of 15°C / min under an argon atmosphere, demold it to obtain an ingot, and then machine it to obtain a high-performance fastener.
[0207] Furthermore, in this example, the prepared high-performance fasteners are heat treated according to the following method to further improve their comprehensive performance. The specific method is the same as that in Example 1.
[0208] Comparative Example 3
[0209] This example is basically the same as Example 1, except that:
[0210] The ceramic doped master alloy in this example is prepared by the following method:
[0211] 1) Preparation of g-C3N4 by calcining urea:
[0212] Place urea in a muffle furnace, heat to 580 °C at 10 °C / min, and calcine for 3.5 h to obtain g-C3N4;
[0213] 2) 0.85 g g-C3N4, 0.0147 mol butyl titanate, and 0.005 mol aluminum acetate were mixed and ground for 60 min, and the resulting mixture was calcined at 650°C for 2 h, cooled to room temperature, and the product was ground to obtain a g-C3N4-TiAlO composite precursor;
[0214] 3) adding the g-C3N4-TiAlO composite precursor into a tubular vacuum furnace, reacting at 1050° C. for 2 h in a hydrogen atmosphere, cooling to room temperature, and grinding to obtain a Ti(C,N)-(TiAl,Al)N metal ceramic composite;
[0215] 4) Electrolessly coating the metal-ceramic composite with NiWCo alloy to prepare a ceramic-doped master alloy:
[0216] 4-1) washing the Ti(C,N)-(TiAl,Al)N metal ceramic composite prepared in step 3) with a 5% by mass hydrochloric acid solution, then washing with deionized water until neutral, then washing with ethanol, and drying at 90° C.;
[0217] 4-2) The Ti(C,N)-(TiAl,Al)N metal ceramic composite pretreated in step 4-1) was added to a 12 g / L SnCl2 solution for 10 min, taken out, washed with deionized water, dried, added to the plating solution, stirred for 5 min, heated to 75°C, the pH value of the plating solution was controlled to 10, and the plating was performed for 60 min. After the completion, it was allowed to stand for 10 min, filtered, and the solid product was washed with deionized water and dried at 60°C for 5 h to obtain a ceramic-doped intermediate alloy.
[0218] In step 4-2), the loading amount of Ti(C,N)-(TiAl,Al)N metal ceramic composite in the plating solution is 10 g / L plating solution; the components of the plating solution include: 30 g / L nickel sulfate, 10 g / L sodium tungstate, 12 g / L cobalt sulfate, 40 g / L sodium hypophosphite, 20 g / L sodium citrate, 10 g / L ammonium chloride, and 25 g / L EDTA.
[0219] Comparative Example 4
[0220] This example is basically the same as Example 1, except that:
[0221] The ceramic doped master alloy in this example is prepared by the following method:
[0222] 1) preparing g-C3N4 by calcining urea, the specific steps are the same as those in Example 1;
[0223] 2) Using g-C3N4 to prepare a g-C3N4-TiAlFeO composite precursor, the specific steps are the same as those in Example 1;
[0224] 3) Using the g-C3N4-TiAlFeO composite precursor, a Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite was prepared by a thermal reduction method, and the specific steps were the same as those in Example 1;
[0225] Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite was used as ceramic doped master alloy.
[0226] Comparative Example 5
[0227] This example is basically the same as Example 1, except that:
[0228] The ceramic doped master alloy in this example is prepared by the following method:
[0229] 1) preparing g-C3N4 by calcining urea, the specific steps are the same as those in Example 1;
[0230] 2) Using g-C3N4 to prepare a g-C3N4-TiAlFeO composite precursor, the specific steps are the same as those in Example 1;
[0231] 3) Using the g-C3N4-TiAlFeO composite precursor, a Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite was prepared by a thermal reduction method, and the specific steps were the same as those in Example 1;
[0232] 4) Electrolessly coating the metal-ceramic composite with Ni to prepare a ceramic-doped master alloy:
[0233] 4-1) washing the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite prepared in step 3) with a 5% by mass hydrochloric acid solution, then washing with deionized water until neutral, then washing with ethanol, and drying at 90° C.;
[0234] 4-2) The Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite pretreated in step 4-1) was added to a 12 g / L SnCl2 solution for 10 min, taken out, washed with deionized water, dried, added to the plating solution, stirred for 5 min, heated to 75°C, the pH value of the plating solution was controlled to 10, and the plating was performed for 60 min. After the completion, it was allowed to stand for 10 min, filtered, and the solid product was washed with deionized water and dried at 60°C for 5 h to obtain a ceramic doped intermediate alloy.
[0235] In step 4-2), the loading amount of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite in the plating solution is 10 g / L plating solution; the components of the plating solution include: 30 g / L nickel sulfate, 40 g / L sodium hypophosphite, 20 g / L sodium citrate, 10 g / L ammonium chloride, and 25 g / L EDTA.
[0236] Comparative Example 6
[0237] This example is basically the same as Example 1, except that:
[0238] In this example, the specific steps of heat treating the prepared high-performance fastener according to the following method include:
[0239] S1. Keep the high-performance fastener at 850℃ for 4 hours, then oil cool to 155℃ and keep it for 2 hours;
[0240] S2, cool down to 750℃, keep warm for 1h, and oil cool to 80℃;
[0241] S3. Heat to 200°C for tempering treatment, keep warm for 3 hours, and then air cool to room temperature to obtain a high-performance fastener product after heat treatment.
[0242] The high-performance fastener products after heat treatment prepared in the examples and comparative examples were made into test specimens, and the following performance characterization and testing were performed.
[0243] 1. Reference Figure 1 , is the XRD spectrum of the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite prepared in Example 1.
[0244] 2. Normal temperature strength and hardness performance test
[0245] Tensile strength test standard "GB / T32498-2016 Room temperature test method for tensile test of metal matrix composite materials";
[0246] Hardness test: Use micro Vickers hardness tester to test.
[0247] The test results are shown in Table 1 below:
[0248] Table 1
[0249] Tensile strength / MPa Yield strength / MPa Elongation after break / % <![CDATA[Vickers hardness / HV 0.1 > Example 1 1452 1361 11.3 1341 Example 2 1423 1334 11.9 1335 Example 3 1461 1366 11.1 1344 Comparative Example 1 741 694 14.2 684 Comparative Example 2 813 762 13.7 751 Comparative Example 3 1133 1062 13.3 1046 Comparative Example 4 929 871 13.6 858 Comparative Example 5 1191 1116 12.7 1100 Comparative Example 6 1446 1339 12.1 955
[0250] From the test results in Table 1, it can be seen that Examples 1-3 have very high strength and hardness. In Comparative Example 1, no ceramic-doped intermediate alloy is added, and the comprehensive performance decreases the most. Although ceramic particles TiC are added in Comparative Example 2, the defects of poor wettability with the steel matrix and difficult dispersion are not solved, so the effect of TiC on improving the strength and hardness of the matrix is not effectively exerted. The ceramic-doped intermediate alloy in Comparative Example 3 does not contain Fe, which affects the improvement of wettability between it and the steel matrix, resulting in a decrease in comprehensive performance. The ceramic-doped intermediate alloy in Comparative Example 4 is not coated with an alloy plating layer, which also affects its uniform dispersion in the steel matrix, resulting in a significant decrease in strength and hardness. Comparative Example 5 uses a pure nickel plating layer to coat the ceramic-doped intermediate alloy. Compared with Comparative Example 4, the overall performance is significantly improved, but it is still lower than that of Example 1, mainly due to the lack of reinforcement effect of the W element. In Comparative Example 6, BC co-penetration treatment is not performed, and the surface hardness is greatly reduced.
[0251] 3. High temperature strength test
[0252] According to the standard: GB / T 228.2-2015 Metallic material tensile test Part 2: High temperature test method, the high temperature tensile strength test was carried out. The test results are shown in Table 2 and Figure 2 As shown:
[0253] Table 2
[0254]
[0255] It can be seen from the test results in Table 2 that Examples 1-3 have very good high temperature strength, while Comparative Examples 1-6 show varying degrees of decline.
[0256] 4. High temperature wear test
[0257] The MFT-5000 reciprocating friction and wear tester was used. The test conditions were: Ar gas protection atmosphere, friction load 20N, reciprocating frequency 1Hz, friction time 30min, friction stroke 15mm, and the friction pair was a corundum ball. The test was conducted at 400℃, 500℃, and 600℃ respectively. The weight before and after wear was measured using an analytical balance, and the wear amount was calculated as: weight before wear - weight after wear. The test results are shown in Table 3 and Figure 3 As shown:
[0258] Table 3
[0259]
[0260] It can be seen from the test results in Table 2 that Examples 1-3 have very good wear resistance, while Comparative Examples 1-6 show varying degrees of decline.
[0261] 5. Corrosion resistance test
[0262] According to the standard: GB / T 19292.4-2018, the sample was placed in a salt spray test machine and an accelerated corrosion test was carried out in a 35°C, 5wt% NaCl solution to calculate the corrosion rate r corr :
[0263] The unit is micrometer per year (μm / a);
[0264] Where Δm is the weight loss, unit is g, A is the surface area of the sample, unit is m 2 ; ρ is the surface density of the sample, unit is g / cm 3 ; t is the exposure time, unit: year (a);
[0265] The test results are shown in Table 4 below:
[0266] Table 4
[0267]
[0268] It can be seen from the test results in Table 4 that Examples 1-3 have excellent corrosion resistance, and the corrosion resistance of Comparative Example 6 is significantly reduced due to the lack of BC surface co-penetration treatment; in Comparative Examples 1-5, the corrosion resistance also decreases to varying degrees due to the decrease in the comprehensive performance of the base material and the decrease in the bonding strength with the BC penetration layer.
[0269] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A high performance fastener, characterized in that: The composition of the raw materials for its preparation is as follows by weight percentage: C: 0.12-0.33%, Si: 0.23-0.48%, Mn: 0.62-0.77%, Cr: 2.32-4.14%, Ni: 4.11-6.32%, Re: 0.005-0.022%, ceramic-doped master alloy: 4.2-13.5%, the balance is Fe and unavoidable impurity elements; The ceramic-doped master alloy is prepared by the following method: 1) Preparation of g-C3N4 by calcining urea; 2) Preparation of g-C3N4-AlFeO composite precursor using g-C3N4; 3) Preparation of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite by thermal reduction method using g-C3N4-AlFeO composite precursor; 4) The metal-ceramic composite is coated with NiWCo alloy by chemical plating to prepare the ceramic-doped master alloy.
2. The high performance fastener according to claim 1, characterized in that: The ceramic-doped master alloy is prepared by the following method: 1) Preparation of g-C3N4 by calcination of urea: Place urea in a muffle furnace, heat to 550-650°C at 5-10°C / min, and calcine for 3-5h to obtain g-C3N4; 2) Preparation of g-C3N4-TiAlFeO composite precursor using g-C3N4: 0.42-3.15 g g-C3N4, 0.0073-0.0294 mol butyl titanate, 0.03-0.2 mol ferric acetate, and 0.0025-0.01 mol aluminum acetate are mixed and ground for 45-90 min, the resulting mixture is calcined at 600-700 ° C for 1-4 h, cooled to room temperature, and the product is ground to obtain a g-C3N4-TiAlFeO composite precursor; 3) Preparation of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite by thermal reduction method using g-C3N4-TiAlFeO composite precursor: The g-C3N4-TiAlFeO composite precursor is added into a tubular vacuum furnace, reacted at 950-1150°C for 1-4 hours in a hydrogen atmosphere, cooled to room temperature, and ground to obtain a Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite; 4) Electrolessly coating the metal-ceramic composite with NiWCo alloy to prepare the ceramic-doped master alloy: 4-1) washing the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite prepared in step 3) with a hydrochloric acid solution, then washing with deionized water until neutral, then washing with ethanol, and drying; 4-2) The Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite pretreated in step 4-1) is added to a 5-20 g / L SnCl2 solution for 5-25 min, taken out, washed with deionized water, added to the plating solution, stirred for 2-10 min, heated to 70-80°C, and the pH value of the plating solution was controlled to 10-11. The plating was performed for 40-90 min, and then allowed to stand for 5-20 min. After the completion, the solid product was filtered, washed with deionized water, and dried to obtain a ceramic doped intermediate alloy.
3. The high performance fastener according to claim 2, characterized in that: In step 4-2), the loading amount of the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite in the plating solution is 5-25 g / L of plating solution.
4. The high performance fastener according to claim 3, characterized in that: The components of the plating solution include: 20-38 g / L nickel sulfate, 5-15 g / L sodium tungstate, 6-18 g / L cobalt sulfate, 30-45 g / L sodium hypophosphite, 10-30 g / L sodium citrate, 6-15 g / L ammonium chloride, and 13-34 g / L EDTA.
5. The high performance fastener according to claim 4, characterized in that: The composition of the ceramic-doped master alloy is as follows by weight percentage: Ti: 7.05-19.24%, Al: 1.91-4.40%, Ni: 12.06-24.25%, W: 7.18-12.45%, Co: 5.43-8.62%, C: 3.16-6.04%, N: 4.95-8.97%, and the balance is Fe and inevitable impurity elements.
6. The high performance fastener according to claim 5, characterized in that: The ceramic-doped master alloy is prepared by the following method: 1) Preparation of g-C3N4 by calcination of urea: Place urea in a muffle furnace, heat to 580 °C at 10 °C / min, and calcine for 3.5 h to obtain g-C3N4; 2) Preparation of g-C3N4-TiAlFeO composite precursor using g-C3N4: 0.85 g g-C3N4, 0.0147 mol butyl titanate, 0.065 mol ferric acetate, and 0.005 mol aluminum acetate were mixed and ground for 60 min, and the resulting mixture was calcined at 650 ° C for 2 h, cooled to room temperature, and the product was ground to obtain a g-C3N4-TiAlFeO composite precursor; 3) Preparation of Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite by thermal reduction method using g-C3N4-TiAlFeO composite precursor: The g-C3N4-TiAlFeO composite precursor was added into a tubular vacuum furnace, reacted at 1050°C for 2 h in a hydrogen atmosphere, cooled to room temperature, and ground to obtain a Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite. 4) Electrolessly coating the metal-ceramic composite with NiWCo alloy to prepare the ceramic-doped master alloy: 4-1) The Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite prepared in step 3) was washed with a 5% by mass hydrochloric acid solution, then washed with deionized water until neutral, then washed with ethanol, and dried at 90°C; 4-2) The Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite pretreated in step 4-1) was added to a 12 g / L SnCl2 solution for 10 min, taken out, washed with deionized water, dried, added to the plating solution, stirred for 5 min, heated to 75°C, and the pH value of the plating solution was controlled to 10. The plating was performed for 60 min. After the completion, it was allowed to stand for 10 min, filtered, and the solid product was washed with deionized water and dried at 60°C for 5 h to obtain a ceramic doped intermediate alloy.
7. The high performance fastener according to claim 6, characterized in that: In step 4-2), the loading amount of the Ti(C,N)-(TiAl,Al)N@Fe metal ceramic composite in the plating solution is 10 g / L plating solution; The components of the plating solution include: 30g / L nickel sulfate, 10g / L sodium tungstate, 12g / L cobalt sulfate, 40g / L sodium hypophosphite, 20g / L sodium citrate, 10g / L ammonium chloride, and 25g / L EDTA.
8. The high performance fastener according to claim 7, characterized in that: The composition of the ceramic-doped master alloy is as follows by weight percentage: Ti: 14.11%, Al: 2.70%, Ni: 17.12%, W: 9.39%, Co: 6.86%, C: 4.52%, N: 7.26%, and the remainder is Fe and inevitable impurity elements.
9. The high performance fastener according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: Step 1: weigh the raw materials according to weight ratio: carbon, silicon, manganese, chromium, nickel, rhenium and ceramic-doped master alloy; Step 2, smelting: add all raw materials into a vacuum induction furnace, smelt at 1300-1550°C for 20-45min, and then perform LF refining and degassing to obtain molten steel; Step 3: Casting: Cast the molten steel into shape and machine it to obtain high-performance fasteners.
10. A heat treatment method for a high performance fastener according to claim 9, characterized in that: The following steps are involved: S1. Keep the high-performance fasteners at 800-900℃ for 2-6h, then oil cool to 120-180℃ and keep for 1-3h; S2. Surface chemical heat treatment: After grinding, cleaning and drying, high-performance fasteners are placed in a container, embedded with co-penetration powder, sealed, and heated at 850-1000℃ for 8-12h for BC co-penetration; The co-penetration powder is prepared by the following method: according to mass percentage, 20-28% of borax, 10-15% of boron carbide, 3-8% of ammonium chloride, 1.5-5% of potassium fluoroborate, 0.5-2% of yttrium oxide, 0.5-1.5% of lanthanum oxide and the balance of charcoal are mixed, and ball milled for 1-4 hours to obtain the co-penetration powder; S3, cool down to 700-800℃, keep warm for 0.5-3h, oil cool to 70-90℃; S4. Heat to 180-270℃ for tempering, keep warm for 1-5h, and then air cool to room temperature.
Citation Information
Patent Citations
Method for processing high-strength fastener and hot-treating process
CN102260830B
Method for rapidly preparing Ti (Cx, N1-x)-based metal ceramic cutter with high thermal hardness and high strength
CN114737078A
Low-cost high-strength marine atmospheric environment corrosion-resistant bolt for bridge and manufacturing method
CN115537670A